Cross-cultural adaptation and validation of the Athlete Fear Avoidance Questionnaire in Italian university athletes with musculoskeletal injuries. Issue 3 (30th May 2022) - Monticone, Marco; Dover, Geoffrey; Massidda, Myosotis; Giordano, Andrea; Franchignoni, Franco
Abstract : The aim of this study was to translate, culturally adapt and validate an Italian version of the Athlete Fear Avoidance Questionnaire (AFAQ-I). We conducted a cross-sectional evaluation of the psychometric properties of the AFAQ-I in university athletes with musculoskeletal injuries, culturally adapting it in accordance with international standards. Psychometric evaluation included the assessment of structural validity (exploratory factor analysis), internal consistency (Cronbach's alpha and inter-item correlation), test-retest reliability [intraclass correlation coefficient, (ICC) (2, 1)], measurement error and minimum detectable change (MDC). To examine construct validity, we compared (Spearman ρ) the AFAQ-I with a numerical pain rating scale (NPRS), the Pain Catastrophizing Scale (PCS) and the Fear Avoidance Beliefs Questionnaire (FABQ) subscales [FABQ-Physical Activity (FABQ-PA) and FABQ-Work (FABQ-W)]. The AFAQ-I was administered to 133 university athletes with musculoskeletal injuries (95 males and 38 females; mean age 25 years, SD 5; mean average pain duration 5.6 months, SD 8.7). Factor analysis revealed an acceptable 1-factor 10-item solution (explained common variance at minimum rank factor analysis: 0.74) although a couple of items (#6 and 9) presented low factor loadings, suggesting the presence of a small secondary dimension. Cronbach's alpha was 0.78 and the average inter-item correlation was 0.27. ICC (2, 1) was 0.95 and the MDC was 4.4 points. As hypothesized a priori, the AFAQ-I moderately correlated with NPRS (ρ = 0.42), PCS (ρ = 0.59), FABQ-PA (ρ = 0.40) and FABQ-W (ρ = 0.34). In conclusion, the AFAQ-I is a valid Italian translation of AFAQ that demonstrates acceptable psychometric properties. However, we recommend further analysis of the construct definition of the AFAQ and additional examination of its structural validity.